PERANCANGAN SISTEM INFORMASI PENYEWAAN JASA DEKORASI BERBASIS WEB PADA GIANLUCA PROJECT - Lorenzo, Ignatius; Tony (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Design of Information System Based Decoration Services Rental Web The Gianluca Project is a plan created to help customers in making bookings and paying for decoration services and helping the Gianluca Project admin in processing booking data and paying for decoration services better. The booking process at the Gianluca Project is still using semi-technological methods, namely customer contact directly with the owner through the application Whatsapp. The design of a Web-Based Decoration Service Rental Information System at the Gianluca Project has a features gallery which contains projects that have been done by the Gianluca Project and there are decoration packages that customers can choose from. Information System Design Information System Design uses the development methodology System Development Life Cycle (SDLC) Waterfall. The database used by this application uses a database MySQL. The programming languages ​​used are HTML, CSS and PHP with Framework Bootstrap that generates web apps that are interesting and dynamic. With application web dynamic ones can help the admin in accessing and processing data, as well as helping customers in doing booking and transactions that may affect business development.